First principles calculations of Al AsxP1-x ternary nanocrystal alloying composition - Hussein, Mohammed T. (Iraqi Journal of Physics, 2019)
III-V zinc-blende AlP, AlAs semiconductors and their alloy Aluminum Arsenide phosphide Al AsxP1-x ternary nanocrystals have been investigated using Ab- initio density functional theory (Ab-initio-DFT) at the generalized-gradient approximation (GGA) level with STO-3G basis set coupled with large unit cell method (LUC). The dimension of crystal is found around (1.56 – 2.24) nm at a function of increasing the sizes (8, 16, 54, 64) with different concentration of arsenide (x=0, 0.25, 0.5, 0.75 and 1) respectively. Gaussian 03 code program has been used throughout this study to calculate some of the physical properties such as the electronic properties energy gap, lattice constant, valence and conduction band as well as density of state. Results show that the lattice constant increases with the increasing in the arsenide concentration in the alloy. The total energy, cohesive energy, electron affinity and ionization potential as well as ionicity for these concentrations have been reported.